The cost and value-add of using a financial advisor - Moosa, Abdallah (Department of Finance and Tax, 2021)
This study investigates the quantitative value of advice added by financial advisors in South Africa; where value is measured through return differentials between advised and non-advised investors. A sample of 3189 individual investors from a large South African investment manager was analysed over a period of approximately five years, from 4 August 2014 to 31 July 2019. The primary focus of this study is to determine whether financial advisors create value for investors relative to the cost of advice, by investigating if a significant difference exists between the net of advisor fee returns earned by advised and non-advised investors. It also examines investor trading behaviour and assesses if any significant correlations exist between the number of trades made and returns earned. Current South African literature has a limited consideration of the cost of advice when considering the overall value added by financial advisors and has been found to consider a limited range of investment funds and asset classes. This study examines a range of ten investment funds that cover a range of asset classes and examines investment performance both before and after advice fees. The data is also analysed to examine the trading behaviour differences with the correlation between trading and investment returns also examined. The results of this study show that overall, the returns generated by non-advised investors are not significantly different from the returns generated by advised investors before advisor fees are considered. When advisor fees are considered, the impact of advisor fees creates a significant difference in performance between advised and non-advised investors; leading to non-advised investors performing the same or better after fees are considered. The trading behaviour showed that advised investors made statistically significantly fewer trades than non-advised investors. The results did not show strong evidence of return differentials arising from the timing of trade decisions, for either advised or non-advised investors.